Towards more disorganised decentralisation? Collective bargaining in the public sector under pay restraint. Issue 1 (January 2017) - Grimshaw, Damian; Johnson, Mat; Marino, Stefania; Rubery, Jill
Abstract: While sector‐level collective bargaining can provide the institutional leverage to sustain and improve employment standards, a proliferation of disorganised local settlements may reduce its effectiveness. This article examines this proposition for local government in the UK, highlights the risks of a 'destructive' disorganisation of employment relations and calls for a renewal of articulation mechanisms between sector and local levels of collective bargaining.